Actitudes maternales en la enseñanza remota y el aprendizaje en personal social en los niños de la Institución Educativa Inicial N° 602, San Juan 2022 - Garcia Saavedra, Delia Isabel (2024)
The study was carried out with the purpose of determining if maternal attitudes in remote teaching are significantly related to the learning of social personnel in children of the educational institution No. 602 San Juan. In the methodology, a quantitative approach of correlational scope was used with a non-experimental design of a cross[1]sectional type. The study included a sample of 76 children with their respective mothers, to whom a questionnaire and an observation guide previously validated by expert judgment were applied. The results allowed us to conclude that maternal attitudes in remote teaching are significantly related to the learning of social personnel in the children of the studied population. This according to the statistical value of Student's t = 6.335; p-value (bilateral significance) = 0.000, this value being less than 0.05.